What do pregnant women think about influenza disease and vaccination practices in selected countries. Issue 7 (3rd July 2021) - Arriola, Carmen S.; Suntarattiwong, Piyarat; Dawood, Fatimah S.; Soto, Giselle; Das, Prabir; Hunt, Danielle R.; Sinthuwattanawibool, Chalinthorn; Kurhe, Kunal; Thompson, Mark G.; Wesley, Meredith G.; Saha, Siddhartha; Hombroek, Danielle; et al.
ABSTRACT: Introduction : We evaluated knowledge, attitudes, and practices (KAP) related to influenza and influenza vaccination among pregnant women in three selected countries. Methods : During 2017, pregnant women seeking antenatal care at hospitals at participating sites were enrolled. We described characteristics and responses to KAP questions. We also evaluated predictors associated with influenza vaccination during pregnancy at sites with substantial influenza vaccine uptake by multivariable logistic regression. Results : Overall, 4, 648 pregnant women completed the survey. There were substantial differences among the three survey populations; only 8% of the women in Nagpur had heard of influenza, compared to 90% in Lima and 96% in Bangkok ( p -value<0.01). Despite significant differences in sociodemographic characteristics in the three populations, most participants across sites who were aware of influenza prior to study enrollment believe they and their infants are at risk of influenza and related complications and believe influenza vaccination is safe and effective. Half of women in Lima had verified receipt of influenza vaccine compared to <5% in Bangkok and Nagpur ( p < .05). For further analysis conducted among women in Lima only, household income above the poverty line (aOR: 1.38; 95%CI: 1.01, 1.88), having 8+ antenatal visits, compared to 0–4 (aOR: 2.41; 95%CI: 1.39, 2.87, respectively), having 0 children, compared to 2+ (aOR: 1.96; 95%CIs: 1.23, 3.12), and vaccination recommended by a health-care provider (aOR: 8.25; 95%CI: 6.11, 11.14) were strongly associated with receipt of influenza vaccine during pregnancy. Conclusions : Our findings identify opportunities for targeted interventions to improve influenza vaccine uptake among pregnant women in these settings.